2014
DOI: 10.2525/ecb.52.161
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Saving Night Temperature Regime for Satsuma Mandarins (Citrus unshiu Marc.) Grown in a Plastic House with Heating. I. Effect of Temperature and Water Condition on Fruit Growth and Quality

Abstract: In this study, we discussed how temperature and other environmental factors affect the fruit growth and quality of Satsuma mandarin grown in a plastic house with heating. At 14 23°C, the average nighttime air temperature was positively correlated with the standardized fruit growth rate (GRFSt) in the young stage. In contrast, GRFSt was clearly depressed with a daytime air temperature at around 30°C, and the optimum air temperature for active fruit growth was 25°C. Moreover, in the middle and mature stages, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Similar results were obtained in the fruit quality except fruit rind color and fruit yield (Table 3). These results were not inconsistent with our previous study, where no significant correlation was observed among nighttime temperatures during 60 120 DAFB and fruit soluble sugar content and titratable acidity at 180 DAFB (Yano et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar results were obtained in the fruit quality except fruit rind color and fruit yield (Table 3). These results were not inconsistent with our previous study, where no significant correlation was observed among nighttime temperatures during 60 120 DAFB and fruit soluble sugar content and titratable acidity at 180 DAFB (Yano et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…To clarify the water and carbon balances of each fruit during active fruit growth, four repeated short-term studies were conducted at 60, 71, 100, and 120 DAFB. The days were at the cell enlargement period as stage II (Kikuchi et al, 1964), and at young and middle stages (Yano et al, 2014). Figure 1 shows the average air temperature (Ta) and…”
Section: Environmental Conditions For Calculating Fruit Water and Carmentioning
confidence: 99%
“…In addition, the delayed decrease in the juice-acid content is accompanied by a depression in fruit volume enlargement (Kurihara, 1969(Kurihara, , 1971Utsunomiya et al, 1982;Inoue and Chien, 1988). In Satsuma mandarins grown in a plastic house with heating which is harvested fruit at summer, the nighttime air temperature was considered to be within the suitable range for fruit growth (20 25°C) at stage III (Yano et al, 2014). In this case, fruit with excessive acid content is rarely produced as long as water is managed precisely.…”
Section: Discussionmentioning
confidence: 99%
“…A possible energy-saving temperature regime for Satsuma mandarins grown in a plastic house with heating has been developed. Firstly, at 60 90 DAFB, it is necessary to control 25°C in the daytime (Yano et al, 2014) and not to be lower than 20°C at night (Fig. 4E).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation